2022
DOI: 10.1039/d2ce00124a
|View full text |Cite
|
Sign up to set email alerts
|

The synergistically enhanced activity and stability of layered manganese oxide via the engineering of defects and K+ ions for oxygen electrocatalysis

Abstract: Structural defects and interlayered ions are two classic architectures that regulate the electrochemical activity of layered manganese oxides. However, the synergistic effect of defects and interlayered ions and how it...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…While some Mn oxides were proposed to be sufficiently stable, [89,135,136] other Mn oxides, to which the layered oxides usually belong, suffer from insufficient stability. [50,[137][138][139] The lack in stability is often inferred from electrochemical data alone, this was found to be insufficient.…”
Section: Sample Parametermentioning
confidence: 99%
“…While some Mn oxides were proposed to be sufficiently stable, [89,135,136] other Mn oxides, to which the layered oxides usually belong, suffer from insufficient stability. [50,[137][138][139] The lack in stability is often inferred from electrochemical data alone, this was found to be insufficient.…”
Section: Sample Parametermentioning
confidence: 99%
“…Among these efforts, researchers have shown that surface coating remains as an effective and facile route. They have developed different inorganic and polymeric coatings via wet chemistry vapor-phase processes showing superior performance on NMC811 [30][31][32]. In the past decade, atomic layer deposition (ALD) has emerged as a unique vapor-phase technique enabling high-quality conformal and uniform films over either electrode powders or prefabricated electrodes [33,34].…”
Section: Introductionmentioning
confidence: 99%